Physics model for wringing of wet cloth. (27th September 2016) - Rahmayanti, Handika Dany; Utami, Fisca Dian; Abdullah, Mikrajuddin
Abstract: One activity that has been performed by human beings for a long time is washing clothes. Before the invention of the washing machine, clothes were washed by hand and then wrung before drying in the open air. When observed carefully, the wringing of cloth presents some interesting phenomena. However, there are no reports on the physical modelling of this very old activity. This paper reports a simple model to explain the discharge of water from clothes when squeezed. A simple tool was also designed to retrieve data to confirm the theory. We found that the theoretical predictions accurately explained the experimental results. The experiments were conducted on two types of cloth: towels and batik cloth. We also obtained a universal curve to which all the data converged.